2011
DOI: 10.1124/dmd.111.042101
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biliary Clearance Should Be Predicted by Intrinsic Biliary Clearance in Sandwich-Cultured Hepatocytes

Abstract: ABSTRACT:It has been reported that in vivo biliary clearance can be predicted using sandwich-cultured rat and human hepatocytes. The predicted apparent biliary clearance (CL bile, app ) from sandwichcultured rat hepatocytes (SCRH) based on medium concentrations correlates to in vivo CL bile, app based on plasma concentrations of angiotensin II receptor blockers (ARBs), HMG-CoA reductase inhibitors (statins), ␤-lactam antibiotics, and topotecan. However, the predicted biliary clearance from SCRH was 7-to 300-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…Advancements have been made in using this in vitro technique for predicting biliary clearance (Abe et al, 2009), but the robustness of the method is still to be extensively tested with a wide range of drugs. However, appreciation of the intracellular drug concentrations and calculation of an in vitro biliary intrinsic clearance may see the method emerge as a truly predictive tool (Nakakariya et al, 2012). Nonetheless, preclinical in vivo data retain an extremely important role in facilitating the understanding and contextualization of the risks associated with human pharmacokinetic predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements have been made in using this in vitro technique for predicting biliary clearance (Abe et al, 2009), but the robustness of the method is still to be extensively tested with a wide range of drugs. However, appreciation of the intracellular drug concentrations and calculation of an in vitro biliary intrinsic clearance may see the method emerge as a truly predictive tool (Nakakariya et al, 2012). Nonetheless, preclinical in vivo data retain an extremely important role in facilitating the understanding and contextualization of the risks associated with human pharmacokinetic predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts to scale rat in vivo CL bile from rat SCH efflux, incorporating fu blood , for the biliary cleared compound set resulted in 1.6-fold (digoxin), 3.5-fold (fexofenadine), and 15-to 17-fold (rosuvastatin) underpredictions (Annaert et al, 2001;Turncliff et al, 2006;Fukuda et al, 2008;Nakakariya et al, 2012). Nakakariya et al (2012) have recently shown that biliary clearance predictions from rat SCH can be considerably improved by predicting biliary intrinsic clearance using liver tissue drug concentrations and free intracellular concentrations in rat SCH. Predicting rat CL bile using rat SCH efflux in the traditional manner yielded underpredictions ranging from 7-fold to 300-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting rat CL bile using rat SCH efflux in the traditional manner yielded underpredictions ranging from 7-fold to 300-fold. Predicting intrinsic biliary efflux using intracellular SCH and liver concentrations improved the results, giving underpredictions with an average fold error of 4.5, representing the most successful in vitro method to date for the prediction of biliary clearance (Nakakariya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studying hepatobiliary uptake and secretion of bile acids in vivo is difficult. Isotopically labeled bile acids have been used to study bile acid uptake and secretion in the isolated perfused rat liver (7,8) and conscious dogs (9), and sandwich cultures have been used in attempts to predict the in vivo kinetics of bile acid turnover (10)(11)(12). Clinical methods, such as 99m Tc-mebrofenin SPECT (13) and novel PET tracers for hepatic drug transporters (14), have been used to assess different aspects of hepatic excretory function but not specific bile acid transporters.…”
mentioning
confidence: 99%